2022
DOI: 10.1111/cpr.13279
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahedral framework nucleic acids‐based delivery promotes intracellular transfer of healing peptides and accelerates diabetic would healing

Abstract: Objectives Peptide‐based therapeutics are natural candidates to desirable wound healing. However, enzymatic surroundings largely limit its stability and bioavailability. Here, we developed a tetrahedral framework nucleic acids(tFNA)‐based peptide delivery system, that is, p@tFNAs, to address deficiencies of healing peptide stability and intracellular delivery in diabetic wound healing. Materials and Methods AGEs (advanced glycation end products) were used to treat endothelial cell to simulate cell injury in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Due to the source of its components, tFNAs are highly programmable and easy to modify and label with very low immunogenicity. Recently, studies have found that tFNAs can penetrate different cells to affect their various biological activities. Moreover, our previous research has found that tFNAs or its derivatives could inhibit inflammation via regulating the IL-17 pathway. , Li and his colleagues discovered that tFNAs loaded with resveratrol could suppress inflammation and ameliorate insulin resistance via inhibiting Th1 and Th17 cell activation to reduce the production of IL-17 . In our study, tFNAs were used as a treatment option for AS, and significant therapeutic effects were observed both in vivo and in vitro .…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Due to the source of its components, tFNAs are highly programmable and easy to modify and label with very low immunogenicity. Recently, studies have found that tFNAs can penetrate different cells to affect their various biological activities. Moreover, our previous research has found that tFNAs or its derivatives could inhibit inflammation via regulating the IL-17 pathway. , Li and his colleagues discovered that tFNAs loaded with resveratrol could suppress inflammation and ameliorate insulin resistance via inhibiting Th1 and Th17 cell activation to reduce the production of IL-17 . In our study, tFNAs were used as a treatment option for AS, and significant therapeutic effects were observed both in vivo and in vitro .…”
mentioning
confidence: 62%
“…Tetrahedral frame nucleic acids (tFNAs) are bioactive nanomaterial with tetrahedron-like structures that have been widely studied in the biomedical field. Its editability allows it to carry coding sequence in a framework structure for the treatment of specific diseases. The small size and the negative surface potential of tFNAs determine that it could be quickly ingested by cells to exert various biological effects.…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37] The 3.5% agarose gel electrophoresis (Figure 5C) also demonstrated that NTH consists of four ssDNA molecules. [38][39][40] By dynamic light scattering (DSL), the diameter of the NTH was measured uniformly as 13.54 nm (Figure 5D). In Figure 5E and Figure S8, Supporting Information, we illustrate that NTH exhibits a better support effect on the electrode surface than single-stranded aptamers by comparing their current values when detecting the target.…”
Section: Electrochemical Measurement Of Pd-l1mentioning
confidence: 99%
“…Statistics showed that modification with healing peptide not only further strengthened the ROS-scavenging ability of simple tFNAs from 0.03-fold to 0.67-fold, but also elevated the phosphorylation of ERK1/2 to 1.49-fold, therefore improving the angiogenesis and wound closure processes. 79 Although extensive research studies have confirmed that stable and biocompatible tetrahedral DNA nanostructures are naturally endowed with the ability to neutralize ROS and trigger a rather wide range of cytoprotective pathways, including Akt/Nrf2/HO-1, BCL2/BAX/caspase-3, MAPK/ERK, and NF-κB signaling, the specific trigger mechanism still requires further investigation. First, due to the complicated interaction between ROS and inflammation, the elimination of ROS by DNA self-oxidation can be considered as an important regulatory factor.…”
Section: Anti-inflammatory Applications Of Ros-scavenging Tfnabased D...mentioning
confidence: 99%
“…Statistics showed that modification with healing peptide not only further strengthened the ROS-scavenging ability of simple tFNAs from 0.03-fold to 0.67-fold, but also elevated the phosphorylation of ERK1/2 to 1.49-fold, therefore improving the angiogenesis and wound closure processes. 79…”
Section: Ros-scavenging Tfnas In Anti-inflammatory Therapymentioning
confidence: 99%